Ethnobotanical survey of the uses of Annonaceae around mount Cameroon - Bele, M.Y.; Focho, D.A.; Egbe, E.A.; Chuyong, G.B. (2011)
An ethnobotanical survey was carried out in eight villages around Mount Cameroon in the South West Region of Cameroon. It was focused on determining the uses of the members of the family Annonaceae in this region. Show and Tell Semi-structured Interviews employing a checklist of questions and direct observations were used. The results obtained enable the presentation of the rate of utilization of the members of that family in the study area. At least 70% of the 41 species recorded during field trips from the research area were found to be widely used in traditional medicine by local populations. Some 29 diseases were cured using 24 species. The bark and the wood of these species were the most commonly used plant parts. The check list and ethnomedicinal inventory was developed alphabetically by botanical name, followed by local name, part used, ethnomedicinal uses, mode of usage and information on species availability. Plant specimens were collected, identified, preserved, mounted and voucher was deposited in the Limbe Botanic Garden (SCA) for future references.